Advances in the application of artificial intelligence and internet of things in the management of the Central Sterile Supply Department (人工智能与物联网在消毒供应中心管理中的应用进展) - LIU Xuemei (刘雪梅); WANG Jiamei (王家美); XU Jinhui (徐巾惠) (中西医结合护理)
As the hospital’s core department for infection control, the Central Sterile Supply Department (CSSD) directly influences patient safety and clinical outcomes through its operational efficiency and level of standardization. In recent years, the rapid advances in artificial intelligence (AI) and the Internet of Things (IoT) have opened new opportunities for intelligent upgrades in this field. This paper provides a systematic review of the current applications, existing challenges, and future development trends of AI, IoT, and the Artificial Intelligence of Things (AIoT) within CSSD management, with the goal of offering both theoretical foundations and practical guidance for the intelligent transformation of sterile supply services in a smart healthcare system. (消毒供应中心(CSSD)作为医院感染控制的核心部门, 其管理效率和标准化水平直接影响医疗安全与患者预后。近年来, 随着人工智能(AI)与物联网(IoT)技术的迅速发展, CSSD的智能化升级迎来了新的机遇。本文系统综述了AI、IoT以及智能物联网(AIoT)在CSSD管理中的应用现状, 分析当前面临的挑战, 并探讨未来发展趋势, 旨在为智慧医疗体系中CSSD的智能化建设提供理论依据和实践参考, 推动其在医疗质量管理中的应用与发展。)